PEMBIAYAAN DALAM PERSPEKTIF HADIS - Abdul Sumarlin; Andi Darussalam (Jurnal Teknologi Pendidikan Madrasah, 2024)
This research is entitled "Financing in the Hadith Perspective", the aim of this research is to find out the types of financing in the hadith perspective, the type of research used is descriptive or exploratory research, in this case it focuses on describing and explaining the types of financing in the hadith perspective, using qualitative approach. Data sources come from official documents of Islamic financial institutions, academic publications, books, articles and literature. This research uses the library research method (library study) which means procedures for collecting information and data with the help of various references such as the Qur'an, books, articles, journals, theses, dissertations which are related to financing in perspective. hadith. The research results show that there are three types of financing, including credit financing, investment financing and education financing.